(untitled) (London Journal of Research In Computer Science and Technology, 2025)
Security issues are becoming more and more important in today’s environment, necessitating increased attention to detail because of the rising dangers of infiltration and dangerous situations. Gas leaks and fires are among the most urgent hazards to residential and commercial safety as they may cause a devastating loss of life and property. Conventional alarm systems that just use sound signals frequently fail to guarantee prompt human reaction, particularly in situations where inhabitants are not present. Using Internet of Things (IoT) devices that are coupled with GSM (Global System for Mobile Communications) technology, this study suggests a real-time gas leak and fire detection system that sends timely SMS notifications. To identify anomalies, the system uses an Atmega644P microprocessor that is interfaced with gas and fire sensors, relays, and buzzers. Through the SIM548C GSM module, which notifies pre-designated emergency contacts via SMS in real time, the system instantly sounds an alarm in the event of a gas leak or fire. This rapid communication mechanism ensures faster response and mitigates potential damage. The increasing importance of intelligent, real-time safety systems in tackling contemporary security issues is highlighted by this review.